Simulated investigation of hump formation on water-harvesting abilities of Stenocara Beetle - Lim, Lester Jun Kai (2016)
For a Namib Desert beetle to survive in the desert, these beetles collect fog droplets through the use of their own body surfaces. One of them is the Stenocara Gracilipes which is known as one of the most efficient fog harvesters among its species. A simulated study was done to determine if a specific arrangement of humps atop a surface affects the rate of fog-harvesting efficiency as reflected by the Stenocara Gracilipes. This comprises the development of an experiment using Unity3D simulation software and C# programming to recreate the formation of fog droplets and various surface formations. Crucial parameters were extracted from various sources to recreate a realistic simulation environment experienced by the beetle. 4 Types of formations were created for the experiment, namely Random, Square, Linear and Epsilon formations. Simulation results have shown that the water-collection efficiency is directly related to the amount of bumps present within the formation. This study concludes that other than surface wettability, formations also play a crucial role in the water-harvesting abilities of the Stenocara Gracilipes.